Effects of early blood pressure lowering on early and long-term outcomes after acute stroke: an updated meta-analysis. - Hongxuan Wang; Yamei Tang; Xiaoming Rong; Hui Li; Rui Pan; Yidong Wang; Ying Peng (PLoS ONE, 2014)
BACKGROUND: Hypertension is common after acute stroke onset. Previous studies showed controversial effects of early blood pressure (BP) lowering on stroke outcomes. The aim of this study is to assess the effects of early BP lowering on early and long-term outcomes after acute stroke. METHODS: A meta-analysis was conducted with prospective randomized controlled trials assessing the effects of early BP lowering on early and long-term outcomes after acute stroke compared with placebo. Literature searching was performed in the databases from inception to December 2013. New evidence from recent trials were included. Outcomes were analyzed as early (within 30 days) and long-term (from 3 to 12 months) endpoints using summary estimates of relative risks (RR) and their 95% confidence intervals (CI) with the fixed-effect model or random-effect model. RESULTS: Seventeen trials providing data from 13236 patients were included. Pooled results showed that early BP lowering after acute stroke onset was associated with more death within 30 days compared with placebo (RR: 1.34 and 95% CI: 1.02, 1.74, p = 0.03). However the results showed that early BP lowering had no evident effect on early neurological deterioration, early death within 7 days, long-term death, early and long-term dependency, early and long-term combination of death or dependency, long-term stroke recurrence, long-term myocardial infarction and long-term CVE. CONCLUSIONS: The new results lend no support to early BP lowering after acute stroke. Early BP lowering may increase death within 30 days after acute stroke.